2012
DOI: 10.1002/da.21919
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Network of Panic Disorder: The Role of the Neuropeptide Cholecystokinin

Abstract: Panic disorder (PD) is characterized by panic attacks, anticipatory anxiety and avoidance behavior. Its pathogenesis is complex and includes both neurobiological and psychological factors. With regard to neurobiological underpinnings, anxiety in humans seems to be mediated through a neuronal network, which involves several distinct brain regions, neuronal circuits and projections as well as neurotransmitters. A large body of evidence suggests that the neuropeptide cholecystokinin (CCK) might be an important mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 182 publications
(339 reference statements)
1
56
0
1
Order By: Relevance
“…Overall, with regard to behavioral effects observed after CCK-4 administration, the present results are in accordance with the extensive body of literature on the panicogenic effects of CCK-4 (see Zwanzger et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, with regard to behavioral effects observed after CCK-4 administration, the present results are in accordance with the extensive body of literature on the panicogenic effects of CCK-4 (see Zwanzger et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Among the available panicogenic agents, the neuropeptide cholecystokinin-tetrapeptide (CCK-4) has been shown to induce panic attacks both in patients with PD and in healthy volunteers (Zwanzger et al, 2012). Moreover, panic symptoms elicited by CCK-4 are attenuated after pharmacological treatment: Several studies have shown that treatment with antidepressants, which currently represent first-line treatment for PD, lead to a reduction of panic experimentally induced by CCK-4 (Bradwejn and Koszycki, 1994;Shlik et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of CCK in panic disorders was in fact originally described in humans. Indeed, intravenous administration of CCK-4 was found to induce panic attacks in both healthy volunteers and in patients suffering from panic disorders (Bradwejn et al , 1990, Zwanzger et al , 2012 and sex-differences have been found in these effects which makes them even more interesting. Moreover, of the two types of CCK receptors identified, CCK2-R is most abundant in the brain and also the receptor mainly thought to induce the observed anxiogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a twin study of Vietnam veterans revealed that about 37.9% of vulnerability to PTSD was genetically related (41). Clinical association studies have identified more than 10 candidate genes for PTSD (5,42), whereas the CCKR-2 gene has been repeatedly associated to panic disorder, another major form of anxiety disorders (10). Moreover, polymorphisms in microRNAs that are associated to panic disorder are also functionally related to the CCKergic system (43).…”
Section: Discussionmentioning
confidence: 99%
“…Stress may dysregulate various neurotransmitter systems in the brain, among which the CCKergic system, including cholecystokinin (CCK) peptides and their receptors, is of a significant importance, based on its dynamic regulation in response to stress (7,8). Actually, the CCKergic system has long been recognized as an anxiogenic factor (7), and CCK peptides were commonly used to induce anxiety in volunteers (9,10). CCK peptides and CCK receptor-2 (CCKR-2) widely distribute in the brain, with the highest level in the limbic system (11), the areas that are critically involved in cognition and emotion (12).…”
mentioning
confidence: 99%